Responses of natural microorganisms to land reclamation and applications of functional microorganisms in biorestoration of coal mining area - Mao, Zhen; Harris, Jim A.; Zhang, Zheyu (MDPI, 2024)
Extensive coal mining causes significant ecological and environmental impacts on the local ecosystem, especially on the terrestrial ecosystem. Mining activities induce the degradation of topsoil physico–chemical characteristics and the succession of soil microbial communities. The soil microbial community is sensitive to soil disturbance and restoration practices, being significant in soil reconstruction and land restoration. Microbes could be effective instruments to restore or reclaim disturbed terrestrial ecosystems and indispensable, unambiguous, indicators to assess reclaimed soils. In the present review, we aimed to provide insight into the effects of mining and subsequent land reclamation on soil microorganisms and the importance and application of microorganisms in the reclamation process. We address changes in the diversity and structure of the soil microbial community after reclamation and discuss the main driving factors of the community. We hypothesize that there is a discernible pattern or regularity in the variation of microbial community composition during the process of restoration succession. By employing the life strategy concept, the study attempts to identify and understand how microbial communities evolve during land reclamation. Land reclamation could improve the nutrients in the soil while increasing the proportion of saprotrophic microorganisms. In community succession, vegetation, soil properties, and reclamation time are key determining factors. Whereas bacteria, fungi, and archaea showed different responses to these factors, as they responded differently to varied soil environments, nutrition, and plants, and occupied different biological niches. Finally, we describe the applications of microorganisms as land reclamation monitors or promoters. This knowledge and understanding can provide comprehensive insight into the soil health condition and strong support for forecasting and decision-making in mine land restoration.
Keywords: soil microbial community; coal mining area; land reclamation; response; application